Doped Tin Dioxide (d-SnO2) and Its Nanostructures: Review of the Theoretical Aspects, Photocatalytic and Biomedical Applications - Pinto, Alexandre H.; Nogueira, Andre E.; Dalmaschio, Cleocir J.; Frigini, Iago N.; de Almeida, Jéssica C.; Ferrer, Mateus M.; Berengue, Olivia M. [UNESP]; Gonçalves, Rosana A.; de Mendonça, Vagner R. (MDPI, 2022)
Nanomaterials based on metal oxides are extensively studied for several applications due to their versatility. Improvements in their performances can be obtained due to specific structural modifications. One possible modification is by doping the crystal structure, which can affect the materials structure and properties, especially in nanosized particles. Electronic features are among the properties that can be modified through the doping process, consequently morphological and optical parameters can also be controlled by this process. In this sense, this review presents some modifications to tin dioxide (SnO2), one the most studied materials, mainly through the doping process and their impact on several properties. The article starts by describing the SnO2 structural features and the computational models used to explain the role of the doping process on these features. Based on those models, some applications of doped SnO2, such as photocatalytic degradation of pollutants, CO2 reduction, and desulfurization of fossil fuels are presented and discussed. Additionally, the review describes many biological applications related to antimicrobial activity for doped SnO2 and its nanostructures. Although most of the examples presented in this article are based on the doped SnO2, it also presents examples related to SnO2 composites with other nanomaterials forming heterojunctions. The metal oxides SnO2, doped-SnO2 and their nanostructures are promising materials, with results reported in many fields presented in this review, such as theoretical and computational chemistry, environmental remediation, nanoparticle morphology control, fossil fuels improvement, and biomedical applications. Although widely explored, there are still fields for innovation and advances with tin dioxide nanostructures, for example, in transparent conducting oxides, in forensics as materials for latent fingerprints visualization, and sensors in medicine for detection of exhaled volatile organic compounds. Therefore, this article aims to be a reference regarding correlating the doping processes and the properties presented by the SnO2 nanostructures.
Keywords: biomedical applications; CO2 photoreduction; desulfurization; nanoparticle; photocatalysis; tin dioxide